The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3389/fmicb.2022.1113601
|View full text |Cite
|
Sign up to set email alerts
|

Influence of structural features and feruloylation on fermentability and ability to modulate gut microbiota of arabinoxylan in in vitro fermentation

Abstract: IntroductionArabinoxylan (AX) is a versatile polysaccharide that shows various effects in modulating gut microbiota and health. The influence of arabinoxylan carbohydrate structural feature and feruloylation on fermentability and the effect of modulation of gut microbiota of AX was not clear.MethodsArabinoxylans from rice bran and corn bran (RAX and CAX), and their deferulyolated counterpart dRAX and dCAX were fermented using an in vitro fermentation model. Structural information was determined based on monosa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…The in vitro fermentation assay was carried out under anaerobic conditions, adhering to the protocol established previously . Stool samples were procured from three healthy individuals, aged between 22 and 28, who were void of any gastrointestinal diseases and had abstained from antibiotic use for a minimum of 3 months preceding the collection.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The in vitro fermentation assay was carried out under anaerobic conditions, adhering to the protocol established previously . Stool samples were procured from three healthy individuals, aged between 22 and 28, who were void of any gastrointestinal diseases and had abstained from antibiotic use for a minimum of 3 months preceding the collection.…”
Section: Methodsmentioning
confidence: 99%
“…The in vitro fermentation assay was carried out under anaerobic conditions, adhering to the protocol established previously. 24 Stool samples were procured from three healthy individuals, aged between 22 and 28, who were void of any gastrointestinal diseases and had abstained from antibiotic use for a minimum of 3 months preceding the collection. Ethical clearance for the study was obtained from the Ethics Committee of Nanchang University, with all procedures being in strict compliance with the guidelines and regulations of the institutional review board (IRB) protocol.…”
Section: In Vitro Fermentationmentioning
confidence: 99%
“…Although these groups of bacteria are not considered to be the primary targets of prebiotics, they have also been shown to have a strong relationship with human health [123]. Li et al (2023) used an in vitro fermentation model to simulate the fermentation of WUAX (RAX and CAX) and their deglycosylated counterparts (dRAX and dCAX) extracted from rice bran and corn bran in the human gut and found that all types of AX significantly increased the relative abundance of Bacteroides, and that the most predominant SCFAs in the fermentation products after 48 h of fermentation were acetic and propionic acids, followed by butyric acid [30]. Likewise, Damen et al (2011) evaluated gut microbiota composition and SCFA production in rats fed WUAX, WEAX, AXOS and their combinations.…”
Section: Improvement Of Gut Healthmentioning
confidence: 99%
“…The gut microbiota can define and regulate host homeostasis by determining nutritional, immune, and neuroendocrine homeostasis [29]. AXs also play a crucial role in regulating the composition of gut microbiota and promoting intestinal health [30], with a variety of bioactivities such as immune and antioxidant enhancement, strengthening of the intestinal epithelial barrier, relief of constipation, and improvement of lipid and glucose metabolism [5][6][7][8][9][10][11][12]. AXs can modulate the profile and function of some of the beneficial bacteria in the human gut microbiota [31].…”
Section: Introductionmentioning
confidence: 99%